The synergy of the traditional plant motif and its cultural values in enhancing place identity of the Muslim royal town - Mohd Khalid, Intan Khasumarlina; Ismail, Nor Atiah; Mohd Tahir, Osman (Maulana Malik Ibrahim State Islamic University of Malang, 2022)
The fast-changing growth of new developments in a Malay Royal Town to create new attractions with various forms of architectural expressions has given a direct impression on the street level, affecting the survival of the buildings along a heritage area. As a result, it will tarnish the original character of the place and disappear the image. A deficit of visual representation for injecting place attachment through the traditional plant motif symbolizes cultural value. This paper aims to identify the qualitative responses to the visual representation of plant motifs in enhancing the royal Town of Kuala Kangsar, conducted semi-structured interview participants based on purposive sampling, including professionals, policymakers, and skilled practitioners categories. The data was analyzed through qualitative coding using Atlas Ti 8.0. The significant findings reveal that the Kalumpang Flower motif, the Melur Flower Motif, and the Motif of Asam Batu leaf is the plant's motif element categorized under the royal image motif, which has a specific meaning related to the historical and cultural background. Most importantly, this finding contributes to assessing the details of the plants' motif representation to assist the city council in preserving the unique and valuable historical heritage of the place image of the Royal Town Kuala Kangsar, Perak.